« Vouloir de la politique » - Isabelle Rivoal (Ateliers d'Anthropologie)
As in the rest of the Arab world, in Lebanon youth designates a period of life situated between childhood and manhood, the latter usually inaugurated by marriage, the arrival of children and the opening of one’s own house. However, in this society marked by confessionalism, young people distinguish themselves by their very strong politicisation. Based on an ethnography of the partisan socialisation of Druze youths, the article shows how youths “detach” themselves from their family positioning in order to become the “army of the president [Walid Joumblatt]”. The youths then get involved in holiday camps, university bodies, party meetings in order to “learn” politics: this learning process includes reading the writings of Kamal Joumblatt, political discussions, involvement in partisan activities, the “surveillance” of territory, availability in order to give the party a visible presence. Whereas heads of family relate to Walid Joumblatt, the lord (bek) of the Mountain, in an extremely codified way during traditional visits, Walid Joumblatt’s relationship with youths in his role as president of the PSP is marked by familiarity and complicity. The political leader is a “maternal uncle” who inspires and guides youths, who are prepared to die for him, while he himself is prepared to die for the “cause” he represents.